An experimental approach to assess the combined effects of multiple stressors on a large vertebrate species - Enrico Pirotta; Catriona M. Harris; Lori H. Schwacke; Len Thomas; Jason B. Allen; Aaron A. Barleycorn; Marco Casoli; Jonathan Crossman; Laura Aichinger Dias; Laura Engleby; Erin LaBrecque; Jenny A. Litz; et al. (Conservation Biology, 2026)
The design of experiments to investigate the combined effects of multiple stressors requires exposing target organisms to multiple combinations of stressor doses. Concurrent manipulation of stressors is often infeasible with wildlife, but long‐lasting health effects allow individual health to be used as an integrator of prior stressor exposure. The population of bottlenose dolphins in Barataria Bay, Louisiana, experienced long‐lasting health effects after exposure to oil from the Deepwater Horizon spill. We investigated whether compromised health status affects dolphins’ ability to respond to other stressors, specifically vessel traffic, potentially leading to increased collision risk. We used this case study to develop a hypothesis‐driven experimental approach to assess the combined effects of multiple stressors in a large, long‐lived vertebrate species. We conducted controlled vessel approaches to test whether the health status of targeted dolphins affected their behavioral responses. Our results highlighted some effects of health, suggesting that oil spills may exacerbate the effects of other stressors in coastal populations. For example, lung disease was associated with a delayed dive response, which could affect the ability to vertically avoid vessels and lead to increased collision risk. However, health effects on response probability were overall smaller than anticipated, and other contextual variables (e.g., sex, age, calf presence, prior experience, and exposure context) contributed to response variability. Our work demonstrated the value of formalizing stressor interactions as multidimensional dose–response functions and showed the feasibility of an experimental, multiple‐stressor study in a wild system in which individual health status can be used as an integrator of prior stressor exposure. This approach has broad implications for other species that are difficult to handle experimentally. The quantification and management of the cumulative risk from multiple stressors on wildlife will require a combination of empirical and mechanistic approaches to inform long‐term, population consequences.

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Urbanization controls surface energy partitioning and energy balance closure across the New York City urban-exurban gradient - Wenge Ni-Meister; Qian Allen Luo; Jason Covert; Prathap Ramamurthy; Lixin Lu (Urban Climate, 2026)

Millet stable isotopes reveal the advance of agricultural practices in the core political regions of early imperial China - Jingwen Liao; Edward Allen; Amanda G. Henry; Jason E. Laffoon; Ming Li; Daiyun Liu; Pengfei Sheng (CATENA, 2025)

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Pre‐existing phytoplankton biomass concentrations shape coastal plankton response to fire‐generated ash leachate - Nicholas Baetge; Kimberly H. Halsey; Erin J. Hanan; Michael J. Behrenfeld; Allen J. Milligan; Jason R. Graff; Parker Hansen; Craig A. Carlson; Rene M. Boiteau; Eleanor C. Arrington; Jacqueline Comstock; Elisa R. Halewood; et al. (Limnology and Oceanography, 2025)
Climate‐driven warming is projected to intensify wildfires, increasing their frequency and severity globally. Wildfires are an increasingly significant source of atmospheric deposition, delivering nutrients, organic matter, and trace metals to coastal and open ocean waters. These inputs have the potential to fertilize or inhibit microbial growth, yet their ecological impacts remain poorly understood. This study examines how ash leachate, derived from the 2017 Thomas Fire in California and lab‐produced ash from Oregon vegetation, affects coastal plankton communities. Shipboard experiments off the California coast examined how pre‐existing plankton biomass concentrations mediate responses to ash leachates. We found that ash leachate contained dissolved organic matter (DOM) that significantly increased bacterioplankton specific growth rates and DOM remineralization rates but had a negligible effect on bacterioplankton growth efficiency, suggesting low DOM bioavailability. Furthermore, ash‐derived DOM had a higher potential to accumulate in high biomass water, where pre‐existing DOM substrates may better support bacterial metabolism. Ash leachate had a neutral to negative effect on phytoplankton division rates and decreased microzooplankton grazing rates, particularly in low biomass water, leading to increased phytoplankton accumulation. Nanoeukaryotes accumulated in low biomass water, whereas picoeukaryotes and Synechococcus accumulated in high biomass water. Our findings suggest that the influence of ash deposition on DOM cycling, phytoplankton accumulation, and broader marine food web dynamics depends on pre‐existing biomass levels. Understanding these interactions is critical for predicting the biogeochemical consequences of increasing wildfire activity on marine ecosystems.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Life history, reproductive, and demographic parameters for bottlenose dolphins (Tursiops truncatus) in Sarasota Bay, Florida - Randall S. Wells; Aleta A. Hohn; Michael D. Scott; Jay C. Sweeney; Forrest I. Townsend; Jason B. Allen; Aaron A. Barleycorn; Katherine A. McHugh; Kim Bassos-Hull; Gretchen N. Lovewell; Deborah A. Duffield; Cynthia R. Smith; et al. (Frontiers in Marine Science, 2025)
Studies of the resident community of bottlenose dolphins ( Tursiops truncatus ) of Sarasota Bay, Florida, have been conducted for more than 50 years. Detailed histories have been collected for resident individuals through integrated observations, systematic photographic identification surveys, tagging and tracking, catch-and-release health assessments, remote biopsy sampling, and stranding response. This has produced a unique dataset documenting life history milestones and vital rates of a small cetacean. Analyses of data from 482 resident Sarasota Bay dolphins have revealed estimated maximum life spans of 67 years for females and 52 years for males. For females, predicted age at sexual maturation is 8.5 years, with a predicted age at first reproduction of 9.6 years. Females were observed to give birth when 6-48 years of age, and have been documented with as many as 12 calves, with 45% observed post-separation. Ten percent of females were considered to be reproductively senescent, having gone >13 years without producing a calf. For males, predicted age at sexual maturation is 10 years. Males 10-43 years old sired calves, producing up to 7 calves each. The average calving interval was 3.5 years, albeit with effects due to mother’s age, birth order, and calf survival. Seasonal reproduction was evident, with 81% of births occurring during May-July. Mean annual birth rate was 0.071. Mean annual fecundity was 0.182 births/adult female (defined as females 6 yrs or older). Recruitment rate through reproduction was estimated to be 0.050 based on calves surviving their first year. Immigration was infrequent, with an estimated annual rate of 0.003-0.013. Estimated mean annual maximum loss rate, from mortality, emigration, and changed identification characteristics, was 0.072. Periods of increased loss rates were related to environmental events, and factors that may be important to long-term population resilience were suggested.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Current practices for QSP model assessment: an IQ consortium survey - Jason R. Chan; Richard Allen; Britton Boras; Antonio Cabal; Valeriu Damian; Francis D. Gibbons; Abhishek Gulati; Iraj Hosseini; Jeffrey D. Kearns; Ryuta Saito; Lourdes Cucurull-Sanchez; Jangir Selimkhanov; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Phytoplankton composition from sPACE: Requirements, opportunities, and challenges - Ivona Cetinić; Cecile S. Rousseaux; Ian T. Carroll; Alison P. Chase; Sasha J. Kramer; P. Jeremy Werdell; David A. Siegel; Heidi M. Dierssen; Dylan Catlett; Aimee Neeley; Inia M. Soto Ramos; Jennifer L. Wolny; et al. (Remote Sensing of Environment, 2024)

Spontaneous Behavioural Recovery Following Stroke Relates to the Integrity of Parietal and Temporal Regions - Joseph Y. Nashed; Kaden T. Shearer; Justin Z. Wang; Yining Chen; Elise E. Cook; Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Shirley I. Striver; J. Randal Flanagan; Jason P. Gallivan; Douglas J. Cook (Translational Stroke Research, 2024)

An expert‐based system to predict population survival rate from health data - Lori H. Schwacke; Len Thomas; Randall S. Wells; Teresa K. Rowles; Gregory D. Bossart; Forrest Townsend; Marilyn Mazzoil; Jason B. Allen; Brian C. Balmer; Aaron A. Barleycorn; Ashley Barratclough; Louise Burt; et al. (Conservation Biology, 2024)
Timely detection and understanding of causes for population decline are essential for effective wildlife management and conservation. Assessing trends in population size has been the standard approach, but we propose that monitoring population health could prove more effective. We collated data from 7 bottlenose dolphin ( Tursiops trun catus) populations in the southeastern United States to develop a method for estimating survival probability based on a suite of health measures identified by experts as indices for inflammatory, metabolic, pulmonary, and neuroendocrine systems. We used logistic regression to implement the veterinary expert system for outcome prediction (VESOP) within a Bayesian analysis framework. We fitted parameters with records from 5 of the sites that had a robust network of responders to marine mammal strandings and frequent photographic identification surveys that documented definitive survival outcomes. We also conducted capture–mark–recapture (CMR) analyses of photographic identification data to obtain separate estimates of population survival rates for comparison with VESOP survival estimates. The VESOP analyses showed that multiple measures of health, particularly markers of inflammation, were predictive of 1‐ and 2‐year individual survival. The highest mortality risk 1 year following health assessment related to low alkaline phosphatase (odds ratio [OR] = 10.2 [95% CI: 3.41–26.8]), whereas 2‐year mortality was most influenced by elevated globulin (OR = 9.60 [95% CI: 3.88–22.4]); both are markers of inflammation. The VESOP model predicted population‐level survival rates that correlated with estimated survival rates from CMR analyses for the same populations (1‐year Pearson's r = 0.99, p = 1.52 × 10 –5 ; 2‐year r = 0.94, p = 0.001). Although our proposed approach will not detect acute mortality threats that are largely independent of animal health, such as harmful algal blooms, it can be used to detect chronic health conditions that increase mortality risk. Random sampling of the population is important and advancement in remote sampling methods could facilitate more random selection of subjects, obtainment of larger sample sizes, and extension of the approach to other wildlife species.

Using long-term ecological monitoring to evaluate how climate and human-induced disturbances impact nekton communities in a Northern Gulf of Mexico estuary - Jason A. Garwood; Kira Allen; Megan S. Lamb; Kristy A. Lewis; Jenna Harper; Lee Edmiston (Hydrobiologia, 2023)
Apalachicola Bay, a river-fed estuary in the northeast Gulf of Mexico is experiencing impacts from anthropogenic and climate-induced changes in freshwater inputs and sea level rise. These synergistic pressures have resulted in a historic oyster fishery collapse and the expansion of mangroves, which are displacing native salt marsh. Understanding how these natural and man-made-driven changes have affected the nekton community is essential for the sustainable management of this coastal region. To evaluate changes in nekton occurrence and distribution in Apalachicola Bay, we analyzed 20 years of biological monitoring data. Our results indicated that spatial variation in species’ populations was driven by differences in salinity, while seasonal changes were driven by temperature. Freshwater inflow is the primary driver of salinity, and these differences demonstrated that river flow reductions have the potential to alter nekton communities. The effects of climate-driven droughts and anthropogenic freshwater flow reductions on estuarine community structure highlight the importance of maintaining sufficient river flow for nursery areas, which provide ecosystem services for the region. Ultimately, these findings support the continued need for monitoring programs that track accelerating ecosystem change and provide a clearer understanding for how community composition will respond to global change.

Deep diving by offshore bottlenose dolphins ( Tursiops spp.) - Andreas Fahlman; Reny B. Tyson Moore; Rae Stone; Jay Sweeney; Robyn Faulkner Trainor; Aaron A. Barleycorn; Katherine McHugh; Jason B. Allen; Randall S. Wells (Marine Mammal Science, 2023)
We used satellite‐linked tags to evaluate dive behavior in offshore bottlenose dolphins ( Tursiops spp.) near the island of Bermuda. The data provide evidence that bottlenose dolphins commonly perform both long (>272 s) and deep (>199 m) dives, with the deepest and longest dives being to 1,000 m and 826 s (13.8 min), respectively. The data show a relationship between dive duration and dive depth for dives longer than about 272 s. There was a diurnal pattern to dive behavior, with most dives deeper than 50 m being performed at night; deep diving began at sunset and varied throughout the night. We used the cumulative frequency of dive duration to estimate a behavioral aerobic dive limit (bADL) of around 560–666 s (9.3–11.1 min) in adult dolphins in this population. Dives exceeding the bADL spent significantly longer time in the upper‐most 50 m following a dive as compared with dives less than the bADL. We conclude that the offshore ecotype off Bermuda, unlike the shallow‐diving near‐shore bottlenose dolphin, is a deep‐diving ecotype, and may provide a useful animal model to study extreme diving behavior and adaptations.

The fitness consequences of human‐wildlife interactions on foraging common bottlenose dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida - Kylee M. DiMaggio; Miguel A. Acevedo; Katherine A. McHugh; Krystan A. Wilkinson; Jason B. Allen; Randall S. Wells (Marine Mammal Science, 2023)
Human‐wildlife interactions (HI) are becoming more prevalent with increasing human population. These interactions could have important eco‐evolutionary consequences that become apparent only after observing populations for multiple generations. Here, we analyzed 28 years (1993–2020) of data from the world's longest‐running study of a wild dolphin population to assess the fitness consequences of HI on common bottlenose dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida. We investigated how human‐related foraging activities such as depredation, begging, and patrolling mediate reproductive output and reproductive success of conditioned (HI) and unconditioned (non‐HI) females. The analysis of 84 females and their 286 calves born during 1993–2020 found a confluence of effects on individual fitness. Reproductive output of females engaging in moderate levels of human‐related foraging was 94% greater than that of non‐HI females. However, high frequencies of human‐related foraging had a negative effect on female reproductive success by increasing the risk of calf death up to nine times when compared to non‐HI females, resulting in 31% less calf survival. These findings provide evidence that human‐wildlife interactions have considerable potential to catalyze population‐level changes by altering individual fitness, and demonstrate the value of comprehensive, long‐term data to better understand the ecological and evolutionary implications of human‐wildlife conflict.

Simulating synergistic impacts of climate change and human induced stressors on a northern Gulf of Mexico estuarine food web - Kira L. Allen; Jason A. Garwood; Kelin Hu; Ehab A. Meselhe; Kristy A. Lewis (Frontiers in Marine Science, 2023)
Apalachicola Bay, an estuary located in northwest Florida, is likely to experience a continuing increase in the severity of the effects of changing climate and human-induced stressors, such as sea level rise and changes in freshwater inflow. A coupled hydrodynamic and food web modeling approach was used to simulate future scenarios of freshwater input and sea level rise in Apalachicola Bay from 2020 to 2049 to demonstrate the range of temporal and spatial changes in water temperature, salinity, fisheries species biomasses, total food web biomass and upper trophic level diversity. Additionally, a survey of Apalachicola Bay stakeholders was conducted concurrently with model development to assess stakeholder knowledge and concerns regarding species and environmental changes within the system. Results of the model simulations indicated an increase in water temperature across all scenarios and an increase or decrease in salinity with scenarios of low or high river flow, respectively. These results aligned with the impacts anticipated by stakeholders. White shrimp biomass increased with low river flow and decreased with high river flow, while Gulf flounder biomass decreased across all scenarios. The simulated trends in white shrimp biomass contrasted with stakeholder perceptions. The food web model results also showed an increase in total food web biomass and decrease in upper trophic level diversity across all future scenarios. For all modeled simulations, the largest differences in future environmental variables and species biomasses were between scenarios of low and high river flow, rather than low and high sea level rise, indicating a stronger influence of river flow on the abiotic and biotic characteristics of the estuary. Stakeholders anticipated a future reduction in river flow and increase in sea level rise as negatively impacting the Franklin County economy and stakeholders’ personal interaction with the Apalachicola Bay ecosystem. The use of the ensemble modeling approach combined with the stakeholder survey highlights the use of multiple knowledge types to better understand abiotic and biotic changes in the estuarine system. Results provide insight on the synergistic effects of climate change and human-induced stressors on both the estuarine food web and human community of Apalachicola Bay.

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Surface and diving metabolic rates, and dynamic aerobic dive limits ( dADL ) in near‐ and off‐shore bottlenose dolphins, Tursiops spp., indicate that deep diving is energetically cheap - Andreas Fahlman; Austin S. Allen; Ashley Blawas; Jay Sweeney; Rae Stone; Robyn Faulkner Trainor; Frants H. Jensen; Katherine McHugh; Jason B. Allen; Aaron A. Barleycorn; Randall S. Wells (Marine Mammal Science, 2023)
High‐resolution dive depth and acceleration recordings from nearshore (Sarasota Bay, dive depth Tursiops spp.) were used to estimate the diving metabolic rate (DMR) and the locomotor metabolic rate (LMR, L O 2 /min) during three phases of diving (descent, bottom, and ascent). For shallow dives (depth ≤ 30 m), we found no differences between the two ecotypes in the LMR during diving, nor during the postdive shallow interval between dives. For intermediate (30 m 100 m), the LMR was significantly higher during ascent than during descent and the bottom phase by 59% and 9%, respectively. In addition, the rate of change in depth during descent and ascent (meters/second) increased with maximal dive depth. The dynamic aerobic dive limit (dADL) was calculated from the estimated DMR and the estimated predive O 2 stores. For the Bermuda dolphins, the dADL decreased with dive depth, and was 18.7, 15.4, and 11.1 min for shallow, intermediate, and deep dives, respectively. These results provide a useful approach to understand the complex nature of physiological interactions between aerobic metabolism, energy use, and diving capacity.

Correction: Reading the biomineralized book of life: expanding otolith biogeochemical research and applications for fisheries and ecosystem-based management - Patrick Reis-Santos; Bronwyn M. Gillanders; Anna M. Sturrock; Christopher Izzo; Dion S. Oxman; Jessica A. Lueders-Dumont; Karin Hüssy; Susanne E. Tanner; Troy Rogers; Zoë A. Doubleday; Allen H. Andrews; Clive Trueman; et al. (Reviews in Fish Biology and Fisheries, 2023)

Reading the biomineralized book of life: expanding otolith biogeochemical research and applications for fisheries and ecosystem-based management - Patrick Reis-Santos; Bronwyn M. Gillanders; Anna M. Sturrock; Christopher Izzo; Dion S. Oxman; Jessica A. Lueders-Dumont; Karin Hüssy; Susanne E. Tanner; Troy Rogers; Zoë A. Doubleday; Allen H. Andrews; Clive Trueman; et al. (Reviews in Fish Biology and Fisheries, 2023)
Chemical analysis of calcified structures continues to flourish, as analytical and technological advances enable researchers to tap into trace elements and isotopes taken up in otoliths and other archival tissues at ever greater resolution. Increasingly, these tracers are applied to refine age estimation and interpretation, and to chronicle responses to environmental stressors, linking these to ecological, physiological, and life-history processes. Here, we review emerging approaches and innovative research directions in otolith chemistry, as well as in the chemistry of other archival tissues, outlining their value for fisheries and ecosystem-based management, turning the spotlight on areas where such biomarkers can support decision making. We summarise recent milestones and the challenges that lie ahead to using otoliths and archival tissues as biomarkers, grouped into seven, rapidly expanding and application-oriented research areas that apply chemical analysis in a variety of contexts, namely: (1) supporting fish age estimation; (2) evaluating environmental stress, ecophysiology and individual performance; (3) confirming seafood provenance; (4) resolving connectivity and movement pathways; (5) characterising food webs and trophic interactions; (6) reconstructing reproductive life histories; and (7) tracing stock enhancement efforts. Emerging research directions that apply hard part chemistry to combat seafood fraud, quantify past food webs, as well as to reconcile growth, movement, thermal, metabolic, stress and reproductive life-histories provide opportunities to examine how harvesting and global change impact fish health and fisheries productivity. Ultimately, improved appreciation of the many practical benefits of archival tissue chemistry to fisheries and ecosystem-based management will support their increased implementation into routine monitoring. Graphical abstract

Optimization of 4D Flow MRI Spatial and Temporal Resolution for Examining Complex Hemodynamics in the Carotid Artery Bifurcation - Retta El Sayed; Alireza Sharifi; Charlie C. Park; Diogo C. Haussen; Jason W. Allen; John N. Oshinski (Cardiovascular Engineering and Technology, 2023)

Demographic reporting across a decade of neuroimaging: a systematic review - Elijah Sterling; Hannah Pearl; Zexuan Liu; Jason W. Allen; Candace C. Fleischer (Brain Imaging and Behavior, 2022)
Diversity of participants in biomedical research with respect to race, ethnicity, and biological sex is crucial, particularly given differences in disease prevalence, recovery, and survival rates between demographic groups. The objective of this systematic review was to report on the demographics of neuroimaging studies using magnetic resonance imaging (MRI). The Web of Science database was used and data collection was performed between June 2021 to November 2021; all articles were reviewed independently by at least two researchers. Articles utilizing MR data acquired in the United States, with n ≥ 10 human subjects, and published between 2010–2020 were included. Non-primary research articles and those published in journals that did not meet a quality control check were excluded. Of the 408 studies meeting inclusion criteria, approximately 77% report sex, 10% report race, and 4% report ethnicity. Demographic reporting also varied as function of disease studied, participant age range, funding, and publisher. We anticipate quantitative data on the extent, or lack, of reporting will be necessary to ensure inclusion of diverse populations in biomedical research.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Corrigendum: Rise of the machines: Best practices and experimental evaluation of computer-assisted dorsal fin image matching systems for bottlenose dolphins - Reny B. Tyson Moore; Kim W. Urian; Jason B. Allen; Carolyn Cush; Jason R. Parham; Drew Blount; Jason Holmberg; Jamie W. Thompson; Randall S. Wells (Frontiers in Marine Science, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Rise of the Machines: Best Practices and Experimental Evaluation of Computer-Assisted Dorsal Fin Image Matching Systems for Bottlenose Dolphins - Reny B. Tyson Moore; Kim W. Urian; Jason B. Allen; Carolyn Cush; Jason R. Parham; Drew Blount; Jason Holmberg; Jamie W. Thompson; Randall S. Wells (Frontiers in Marine Science, 2022)
Photographic-identification (photo-ID) of bottlenose dolphins using individually distinctive features on the dorsal fin is a well-established and useful tool for tracking individuals; however, this method can be labor-intensive, especially when dealing with large catalogs and/or infrequently surveyed populations. Computer vision algorithms have been developed that can find a fin in an image, characterize the features of the fin, and compare the fin to a catalog of known individuals to generate a ranking of potential matches based on dorsal fin similarity. We examined if and how researchers use computer vision systems in their photo-ID process and developed an experiment to evaluate the performance of the most commonly used, recently developed, systems to date using a long-term photo-ID database of known individuals curated by the Chicago Zoological Society’s Sarasota Dolphin Research Program. Survey results obtained for the “Rise of the machines – Application of automated systems for matching dolphin dorsal fins: current status and future directions” workshop held at the 2019 World Marine Mammal Conference indicated that most researchers still rely on manual methods for comparing unknown dorsal fin images to reference catalogs of known individuals. Experimental evaluation of the finFindR R application, as well as the CurvRank, CurvRank v2, and finFindR implementations in Flukebook suggest that high match rates can be achieved with these systems, with the highest match rates found when only good to excellent quality images of fins with average to high distinctiveness are included in the matching process: for the finFindR R application and the CurvRank and CurvRank v2 algorithms within Flukebook more than 98.92% of correct matches were in the top 50-ranked positions, and more than 91.94% of correct matches were returned in the first ranked position. Our results offer the first comprehensive examination into the performance and accuracy of computer vision algorithms designed to assist with the photo-ID process of bottlenose dolphins and can be used to build trust by researchers hesitant to use these systems. Based on our findings and discussions from the “Rise of the Machines” workshop we provide recommendations for best practices for using computer vision systems for dorsal fin photo-ID.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Runaway evolution from male‐male competition - Allen J. Moore; Joel W. McGlothlin; Jason B. Wolf (Ecology Letters, 2022)
Wondrously elaborate weapons and displays that appear to be counter to ecological optima are widespread features of male contests for mates across the animal kingdom. To understand how such diverse traits evolve, here we develop a quantitative genetic model of sexual selection for a male signaling trait that mediates aggression in male‐male contests and show that an honest indicator of aggression can generate selection on itself by altering the social environment. This can cause selection to accelerate as the trait is elaborated, leading to runaway evolution. Thus, an evolving source of selection provided by the social environment is the fundamental unifying feature of runaway sexual selection driven by either male‐male competition or female mate choice. However, a key difference is that runaway driven by male‐male competition requires signal honesty. Our model identifies simple conditions that provide clear, testable predictions for empirical studies using standard quantitative genetic methods.

Assessing the Viability of the Sarasota Bay Community of Bottlenose Dolphins - Robert C. Lacy; Randall S. Wells; Michael D. Scott; Jason B. Allen; Aaron A. Barleycorn; Kim W. Urian; Suzanne Hofmann (Frontiers in Marine Science, 2021)
Population models, such as those used for Population Viability Analysis (PVA), are valuable for projecting trends, assessing threats, guiding environmental resource management, and planning species conservation measures. However, rarely are the needed data on all aspects of the life history available for cetacean species, because they are long-lived and difficult to study in their aquatic habitats. We present a detailed assessment of population dynamics for the long-term resident Sarasota Bay common bottlenose dolphin ( Tursiops truncatus ) community. Model parameters were estimated from 27 years of nearly complete monitoring, allowing calculation of age-specific and sex-specific mortality and reproductive rates, uncertainty in parameter values, fluctuation in demographic rates over time, and intrinsic uncertainty in the population trajectory resulting from stochastic processes. Using the Vortex PVA model, we projected mean population growth and quantified causes of variation and uncertainty in growth. The ability of the model to simulate the dynamics of the population was confirmed by comparing model projections to observed census trends from 1993 to 2020. When the simulation treated all losses as deaths and included observed immigration, the model projects a long-term mean annual population growth of 2.1%. Variance in annual growth across years of the simulation ( SD = 3.1%) was due more to environmental variation and intrinsic demographic stochasticity than to uncertainty in estimates of mean demographic rates. Population growth was most sensitive to uncertainty and annual variation in reproduction of peak breeding age females and in calf and juvenile mortality, while adult survival varied little over time. We examined potential threats to the population, including increased anthropogenic mortality and impacts of red tides, and tested resilience to catastrophic events. Due to its life history characteristics, the population was projected to be demographically stable at smaller sizes than commonly assumed for Minimum Viable Population of mammals, but it is expected to recover only slowly from any catastrophic events, such as disease outbreaks and spills of oil or other toxins. The analyses indicate that well-studied populations of small cetaceans might typically experience slower growth rates (about 2%) than has been assumed in calculations of Potential Biological Removal used by management agencies to determine limits to incidental take of marine mammals. The loss of an additional one dolphin per year was found to cause significant harm to this population of about 150 to 175 animals. Beyond the significance for the specific population, demographic analyses of the Sarasota Bay dolphins provide a template for examining viability of other populations of small cetaceans.

Computational Assessment of Valvular Dysfunction in Discrete Subaortic Stenosis: A Parametric Study - Jason A. Shar; Sundeep G. Keswani; K. Jane Grande-Allen; Philippe Sucosky (Cardiovascular Engineering and Technology, 2021)

Staying Alive: Long-Term Success of Bottlenose Dolphin Interventions in Southwest Florida - Katherine A. McHugh; Aaron A. Barleycorn; Jason B. Allen; Kim Bassos-Hull; Gretchen Lovewell; Denise Boyd; Anna Panike; Carolyn Cush; Deborah Fauquier; Blair Mase; Robert C. Lacy; Michelle R. Greenfield; et al. (Frontiers in Marine Science, 2021)
Small cetaceans face persistent threats from fisheries interactions, making effective mitigation a priority for conservation. In southwest Florida, interactions come primarily from small-scale recreational hook and line and trap/pot fisheries, with regional stranding network partners working with federal agency managers to assess and intervene as possible in cases of live animal entanglement. Evaluating success of intervention cases is difficult due to financial and logistical constraints which may preclude detailed follow-up monitoring. Survival over the initial 6 weeks post-release has been used as a marker of short-term success for small-cetacean rescue and/or rehabilitation cases. Early intervention prior to stranding, especially via remote disentanglement or rescue and immediate re-release onsite, can save entangled free-ranging dolphins facing life-threatening anthropogenic injuries. However, given the costs associated with interventions, it is important to understand the benefits of these endeavors not only to save individuals, but also to establish if and how saved individuals contribute to social functioning, survival and reproduction within small, resident populations facing multiple concurrent threats. Here we provide evidence from 27 well-documented common bottlenose dolphin ( Tursiops truncatus ) intervention cases during 1985–2019 where follow-up monitoring over multiple years sheds light on the longer-term success of these efforts and potential benefits to local populations. Nearly all rescued individuals (92%) survived longer than 6 weeks post-release (mean minimum survival period = 5 years, range 0–35 years), with 13 still observed frequently within their prior resident communities, in good physical health, and engaging in normal behavior. Survivorship rates did not decline substantially between 1 and 5 years post-rescue, meaning survival beyond 1 year may be a useful benchmark of long-term success. Rescued females that reached reproductive maturity ( n = 4) have produced 12 post-intervention offspring to date. Social network analysis and demographic modeling applied to cases from the long-term resident community in Sarasota Bay confirmed that animals maintain social connections post-intervention and that interventions result in higher population growth rates. While not every intervention succeeds, this study demonstrates the conservation value of pre-stranding interventions which allow individuals that otherwise would be lost to remain viable and productive members of local populations when prevention of anthropogenic injury is not possible.

In Honour of Professor Cristobal dos Remedios on behalf of the MAWA Trust - Sharyn Watson; Kevin Rozzoli; Anne Keogh; Elizabeth Ahlston; Garry Scroop; Deborah Marriott; Kieran Fallon; Jason Grossman; Toby Allen; Eliza Milliken; Raymond Kidd (Biophysical Reviews, 2020)

Receptor-binding hydrogen–deuterium exchange mass spectrometry as an additional measurement of biosimilarity - Nicholas A. Treuheit; Nicholas F. Crawford; Steven Maki; Jason Payne; Jeff Allen (Journal of Pharmaceutical Investigation, 2020)

Core Competencies for Undergraduates in Bioengineering and Biomedical Engineering: Findings, Consequences, and Recommendations - John A. White; Donald P. Gaver; Robert J. Butera; Bernard Choi; Mary J. Dunlop; K. Jane Grande-Allen; Anna Grosberg; Robert W. Hitchcock; Aileen Y. Huang-Saad; Miiri Kotche; Aaron M. Kyle; Amy L. Lerner; et al. (Annals of Biomedical Engineering, 2020)

Site Fidelity and Habitat Use by Young-of-the-Year Transient Fishes in Salt Marsh Intertidal Creeks - Jason A. Garwood; Dennis M. Allen; Matthew E. Kimball; Kevin M. Boswell (Estuaries and Coasts, 2019)

Amino Acids in Life: A Prebiotic Division of Labor - Jason Allen Davidson (Journal of Molecular Evolution, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Membrane Protein Structure, Function, and Dynamics: a Perspective from Experiments and Theory - Zoe Cournia; Toby W. Allen; Ioan Andricioaei; Bruno Antonny; Daniel Baum; Grace Brannigan; Nicolae-Viorel Buchete; Jason T. Deckman; Lucie Delemotte; Coral del Val; Ran Friedman; Paraskevi Gkeka; et al. (The Journal of Membrane Biology, 2015)

Model structure in observational constraints on transient climate response - Richard J. Millar; Alexander Otto; Piers M. Forster; Jason A. Lowe; William J. Ingram; Myles R. Allen (Climatic Change, 2015)

Effects of flow regime on growth rate in freshwater drum, Aplodinotus grunniens - Stephen J. Jacquemin; Jason C. Doll; Mark Pyron; Michael Allen; Dustin A. S. Owen (Environmental Biology of Fishes, 2015)

Carcass‐recovery rates for resident bottlenose dolphins in Sarasota Bay, Florida - Randall S. Wells; Jason B. Allen; Gretchen Lovewell; Jay Gorzelany; Ruth E. Delynn; Deborah A. Fauquier; Nélio B. Barros (Marine Mammal Science, 2015)

Vulnerability of coastal ecosystems to changes in harmful algal bloom distribution in response to climate change: projections based on model analysis - Patricia M. Glibert; J. Icarus Allen; Yuri Artioli; Arthur Beusen; Lex Bouwman; James Harle; Robert Holmes; Jason Holt (Global Change Biology, 2014)
Harmful algal blooms ( HAB s), those proliferations of algae that can cause fish kills, contaminate seafood with toxins, form unsightly scums, or detrimentally alter ecosystem function have been increasing in frequency, magnitude, and duration worldwide. Here, using a global modeling approach, we show, for three regions of the globe, the potential effects of nutrient loading and climate change for two HAB genera, pelagic Prorocentrum and Karenia , each with differing physiological characteristics for growth. The projections (end of century, 2090–2100) are based on climate change resulting from the A1B scenario of the Intergovernmental Panel on Climate Change Institut Pierre Simon Laplace Climate Model ( IPCC , IPSL ‐ CM 4), applied in a coupled oceanographic‐biogeochemical model, combined with a suite of assumed physiological ‘rules’ for genera‐specific bloom development. Based on these models, an expansion in area and/or number of months annually conducive to development of these HAB s along the NW European Shelf‐Baltic Sea system and NE Asia was projected for both HAB genera, but no expansion ( Prorocentrum spp.), or actual contraction in area and months conducive for blooms ( Karenia spp.), was projected in the SE Asian domain. The implications of these projections, especially for Northern Europe, are shifts in vulnerability of coastal systems to HAB events, increased regional HAB impacts to aquaculture, increased risks to human health and ecosystems, and economic consequences of these events due to losses to fisheries and ecosystem services.

Biomass changes and trophic amplification of plankton in a warmer ocean - Guillem Chust; J. Icarus Allen; Laurent Bopp; Corinna Schrum; Jason Holt; Kostas Tsiaras; Marco Zavatarelli; Marina Chifflet; Heather Cannaby; Isabelle Dadou; Ute Daewel; Sarah L. Wakelin; et al. (Global Change Biology, 2014)
Ocean warming can modify the ecophysiology and distribution of marine organisms, and relationships between species, with nonlinear interactions between ecosystem components potentially resulting in trophic amplification. Trophic amplification (or attenuation) describe the propagation of a hydroclimatic signal up the food web, causing magnification (or depression) of biomass values along one or more trophic pathways. We have employed 3‐D coupled physical‐biogeochemical models to explore ecosystem responses to climate change with a focus on trophic amplification. The response of phytoplankton and zooplankton to global climate‐change projections, carried out with the IPSL Earth System Model by the end of the century, is analysed at global and regional basis, including European seas ( NE A tlantic, B arents S ea, B altic S ea, B lack S ea, B ay of B iscay, A driatic S ea, A egean S ea) and the Eastern Boundary Upwelling System (Benguela). Results indicate that globally and in A tlantic M argin and N orth S ea, increased ocean stratification causes primary production and zooplankton biomass to decrease in response to a warming climate, whilst in the B arents, B altic and B lack S eas, primary production and zooplankton biomass increase. Projected warming characterized by an increase in sea surface temperature of 2.29 ± 0.05 °C leads to a reduction in zooplankton and phytoplankton biomasses of 11% and 6%, respectively. This suggests negative amplification of climate driven modifications of trophic level biomass through bottom‐up control, leading to a reduced capacity of oceans to regulate climate through the biological carbon pump. Simulations suggest negative amplification is the dominant response across 47% of the ocean surface and prevails in the tropical oceans; whilst positive trophic amplification prevails in the A rctic and A ntarctic oceans. Trophic attenuation is projected in temperate seas. Uncertainties in ocean plankton projections, associated to the use of single global and regional models, imply the need for caution when extending these considerations into higher trophic levels.

Ecology of juvenile hawksbills (Eretmochelys imbricata) at Buck Island Reef National Monument, US Virgin Islands - Kristen M. Hart; Autumn R. Sartain; Zandy-Marie Hillis-Starr; Brendalee Phillips; Philippe A. Mayor; Kimberly Roberson; Roy A. Pemberton; Jason B. Allen; Ian Lundgren; Susanna Musick (Marine Biology, 2013)

Isolation of Functional Human Endothelial Cells from Small Volumes of Umbilical Cord Blood - Sa Do Kang; Tim A. Carlon; Alexandra E. Jantzen; Fu-Hsiung Lin; Melissa M. Ley; Jason D. Allen; Thomas V. Stabler; N. Rebecca Haley; George A. Truskey; Hardean E. Achneck (Annals of Biomedical Engineering, 2013)

Nutrient subsidies from nekton in salt marsh intertidal creeks - Dennis M. Allen; Stacy A. Luthy; Jason A. Garwood; Robert F. Young; Richard F. Dame (Limnology and Oceanography, 2013)
Motile organisms are thought to play a role in biogeochemical cycles in tidal systems, but few studies have addressed links between animal activities and dissolved nutrients. Our observations and experiments indicated that movements, feeding, and excretion by fishes and shrimps resulted in subsidies of and to intertidal salt marsh creeks. During low tide, isolated pools inhabited by nekton became biogeochemical hotspots with up to fivefold increases in water column nutrient concentrations. In field experiments, simultaneous measurements in artificial pools and an adjacent natural intertidal pool demonstrated that nekton were sources of during day and night, contributing 17–109% of the net increase in and 3–18% of the in the natural intertidal pool. Nekton residing in intertidal pools generated the equivalent of 5% of the total imported to the creek. At night, nekton in pools contributed the equivalent of 12% of the and 4% of the imported from the subtidal channel. As the tide flooded the intertidal creek, nutrient enriched pool water was pulsed up the creek and into the intertidal basin. Tidally controlled patterns of nekton movements and feeding result in retention and reintroduction of nutrients to the upper reaches of intertidal creek basins. Accordingly, nekton contribute to the recycling of nutrients through a positive feedback loop that may enhance primary production and invertebrate prey within salt marsh creek basins. We conclude that nekton can be important and underappreciated contributors of dissolved nutrients in tidal systems.

Spatial modeling of residential woodsmoke across a non-urban upstate New York region - Jason G. Su; George Allen; Paul J. Miller; Michael Brauer (Air Quality, Atmosphere & Health, 2013)

Mineral Carbonation as the Core of an Industrial Symbiosis for Energy‐Intensive Minerals Conversion - Geoffrey F. Brent; Daniel J. Allen; Brent R. Eichler; James G. Petrie; Jason P. Mann; Brian S. Haynes (Journal of Industrial Ecology, 2012)
Summary The longer term sustainability of the minerals sector may hinge, in large part, on finding innovative solutions to the challenges of energy intensity and carbon dioxide (CO 2 ) management. This article outlines the need for large‐scale “carbon solutions” that might be shared by several colocated energy‐intensive and carbon‐intensive industries. In particular, it explores the potential for situating a mineral carbonation plant as a carbon sink at the heart of a minerals and energy complex to form an industrial symbiosis. Several resource‐intensive industries can be integrated synergistically in this way, to enable a complex that produces energy and mineral products with low net CO 2 emissions. An illustrative hypothetical case study of such a system within New South Wales, Australia, has been constructed, on the basis of material and energy flows derived from Aspen modeling of a serpentine carbonation process. The synergies and added value created have the potential to significantly offset the energy and emission penalties and direct costs of CO 2 capture and storage. This suggests that greenfield minerals beneficiation and metals refining plants should consider closer integration with the power production and energy provision plants on which they depend, together with a carbon solution, such as mineral carbonation, as a critical element of such integration. Other sustainability considerations are highlighted.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Decomposition of urban atmospheric carbon in Sonoran Desert soils - Jason P. Kaye; Sara E. Eckert; Daniel A. Gonzales; Jonathan O. Allen; Sharon J. Hall; Ryan A. Sponseller; Nancy B. Grimm (Urban Ecosystems, 2011)

Comparison of Methods for Chemical Conjugation of an Influenza Peptide to Wild-Type and Cysteine-Mutant Virus-Like Particles Expressed in Pseudomonas fluorescens - Greg T. Cantin; Sol Resnick; Hongfan Jin; Ryan O’Hanlon; Octavio Espinosa; Alex Stevens; Jason Payne; Nicole R. Glenn; Lada Rasochova; Jeffrey R. Allen (International Journal of Peptide Research and Therapeutics, 2011)

Severe Karenia brevis red tides influence juvenile bottlenose dolphin ( Tursiops truncatus ) behavior in Sarasota Bay, Florida - Katherine A. McHugh; Jason B. Allen; Aaron A. Barleycorn; Randall S. Wells (Marine Mammal Science, 2011)
Harmful algal blooms (HABs) are natural stressors in the coastal environment that may be increasing in frequency and severity. This study investigates whether severe red tide blooms, caused by Karenia brevis , affect the behavior of resident coastal bottlenose dolphins in Sarasota Bay, Florida through changes to juvenile dolphin activity budgets, ranging patterns, and social associations. Behavioral observations were conducted on free‐ranging juvenile dolphins during the summer months of 2005–2007, and behavior during red tide blooms was compared to periods of background K. brevis abundance. We also utilized dolphin group sighting data from 2004 to 2007 to obtain comparison information from before the most severe recent red tide of 2005 and incorporate social association information from adults in the study area. We found that coastal dolphins displayed a suite of behavioral changes associated with red tide blooms, including significantly altered activity budgets, increased sociality, and expanded ranging behavior. At present, we do not fully understand the mechanism behind these red tide‐associated behavioral effects, but they are most likely linked to underlying changes in resource availability and distribution. These behavioral changes have implications for more widespread population impacts, including increased susceptibility to disease outbreaks, which may contribute to unusual mortality events during HABs.

Quantifying the Roles of Tidal Volume and PEEP in the Pathogenesis of Ventilator-Induced Lung Injury - Adrian S. Seah; Kara A. Grant; Minara Aliyeva; Gilman B. Allen; Jason H. T. Bates (Annals of Biomedical Engineering, 2011)

A gene encoding an abscisic acid biosynthetic enzyme (LsNCED4) collocates with the high temperature germination locus Htg6.1 in lettuce (Lactuca sp.) - Jason Argyris; María José Truco; Oswaldo Ochoa; Leah McHale; Peetambar Dahal; Allen Van Deynze; Richard W. Michelmore; Kent J. Bradford (Theoretical and Applied Genetics, 2011)

Effects of Central Airway Shunting on the Mechanical Impedance of the Mouse Lung - Benjamin L. Schwartz; Ron C. Anafi; Minara Aliyeva; John A. Thompson-Figueroa; Gilman B. Allen; Lennart K. A. Lundblad; Jason H. T. Bates (Annals of Biomedical Engineering, 2011)

Genetic analysis and uncertain taxonomic status of threatened Foskett Spring speckled dace - William R. Ardren; Jason Baumsteiger; Chris S. Allen (Conservation Genetics, 2010)

Identification, Synthesis and Field Testing of (3Z,6Z,9Z)-3,6,9-Henicosatriene, a Second Bioactive Component of the Sex Pheromone of the Autumn Gum Moth, Mnesampela privata - Paul W. Walker; Geoff R. Allen; Noel W. Davies; Jason A. Smith; Peter P. Molesworth; Anna Nilsson; Fredrik Andersson; Erik Hedenström (Journal of Chemical Ecology, 2009)

Effects of sibutramine and rimonabant in rats trained to discriminate between 22- and 2-h food deprivation - David C. Jewett; Thomas W. Hahn; Travis R. Smith; Britta L. Fiksdal; Jason M. Wiebelhaus; Andrew R. Dunbar; Catherine R. Filtz; Noah L. Novinska; Allen S. Levine (Psychopharmacology, 2009)

Group formation and anemone use in captively reared anemonefish (Amphiprion frenatus) - Eric K. Bollinger; Paul V. Switzer; Jesse Pfammatter; Jason Allen (Ichthyological Research, 2008)

Consequences of injuries on survival and reproduction of common bottlenose dolphins ( Tursiops truncatus ) along the west coast of Florida - Randall S. Wells; Jason B. Allen; Suzanne Hofmann; Kim Bassos‐Hull; Deborah A. Fauquier; Nélio B. Barros; Ruth E. DeLynn; Gretchen Sutton; Victoria Socha; Michael D. Scott (Marine Mammal Science, 2008)
Accurate identification of human‐induced injuries that lead to death or interfere with reproduction is important for marine mammal management, as deaths exceeding established limits can lead to restrictions on fisheries or vessel operations. The fates of cetaceans last seen swimming with attached gear, particularly in pelagic fisheries, or with vessel strike lacerations, have been difficult to predict. Survival and reproduction data from long‐term research on resident common bottlenose dolphins near Sarasota, Florida were examined relative to consequences of fishing gear ingestion, line entanglements, vessel strikes, and amputations of unknown origins. Fishing hooks embedded in the throat, goosebeak, or esophagus, or line wrapped around the goosebeak, generally lead to death. Multiple, constrictive line wraps around fin insertions can lead to amputation, blood loss, impaired mobility, or infection. Dolphins with ingested gear or severe entanglements may swim away with the gear, but likely die later. Propeller injuries involving only soft tissue were often survivable. Some dolphins survived amputations of the distal ends of fins, and continued to reproduce. As a precautionary approach, dolphins with ingested gear or severe constrictive entanglements should be considered mortalities, but extrapolations of findings from coastal bottlenose dolphins to other cetaceans and different gear must be done with caution.

Effects of the dinoflagellates Karlodinium veneficum and Prorocentrum minimum on early life history stages of the eastern oyster (Crassostrea virginica) - Diane K. Stoecker; Jason E. Adolf; Allen R. Place; Patricia M. Glibert; Donald W. Meritt (Marine Biology, 2008)

Environmental Factors Contributing to the Development and Demise of a Toxic Dinoflagellate (Karlodinium veneficum) Bloom in a Shallow, Eutrophic, Lagoonal Estuary - Nathan S. Hall; R. Wayne Litaker; Elizabeth Fensin; Jason E. Adolf; Holly A. Bowers; Allen R. Place; Hans W. Paerl (Estuaries and Coasts, 2008)

The Estimation of Lung Mechanics Parameters in the Presence of Pathology: A Theoretical Analysis - Jason H. T. Bates; Gilman B. Allen (Annals of Biomedical Engineering, 2006)

Patterns of natural and anthropogenic disturbance of the mangroves on the Pacific Island of Kosrae - James A. Allen; Katherine C. Ewel; Jason Jack (Wetlands Ecology and Management, 2001)